Three new chlorinated phenolic glycosides from Przewalskia tangutica. (June 2017) - Zhao, Min; Da-Wa, Zhuo-Ma; Gu, Yu-Cheng; Guo, Da-Le; Ye, Ye; Ding, Li-Sheng; Zhou, Yan
Graphical abstract: Highlights: Three new chlorinated phenolic glycosides were isolated from Przewalskia tangutica . Their structures were elucidated by NMR analysis and chemical methods. Przewatangoside A showed weak cytotoxicity against SMMC-7721. Abstract: Three new chlorinated phenolic glycosides, namely przewatangosides A-C (1 -3 ), along with one known compound, globosumoside A (4 ), were isolated from the whole plants of Przewalskia tangutica . Their structures were unequivocally determined by extensive spectroscopic analysis and chemical method. The cytotoxic activities of the isolated phenolic glycosides (1 -4 ) were evaluated against the five human cancer cell lines A549, MCF-7, SMMC-7721, HepG2 and HL-60. Przewatangoside A (1 ) exhibited weak cytotoxicity against SMMC-7721 with the IC50 value of 38.1 μM. All the tested compounds were inactive (IC50  > 50 μM) to the normal human hepatocyte cell line (L02).